PENERAPAN PENGGUNAAN METODE FUN TEACHING PADA PEMBELAJARAN MATEMATIKA - Frella Silvia; Henry Aditia Rigianti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Low mastery and understanding of mathematical material in students is an important problem that must be solved. Teachers as facilitators try to overcome problems by actively updating the teaching methods applied. The use of the Fun Teaching method has been widely done to improve the learning outcomes of students, especially in mathematics subjects. The purpose of this study is to present a literature review on the application of the use of the Fun Teaching method in improving students' mathematics learning outcomes. The results showed an increase in students' mathematics learning outcomes by applying the Fun Teaching method in learning, as evidenced by the final results of students getting a significant improvement from before.